Arbitrase Daring di Tengah Gelombang Digitalisasi terhadap Analisis Relevansi Tantangan dan Perubahan Proses Hukum - Moch. Gufron Fajar Rezki; Eka Wahyu Setyawan; Nur Qoilun (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
Online arbitration has emerged as a significant innovation in dispute resolution systems in the digital era, as information technology has become the primary foundation for various legal activities. This mechanism offers a new way to resolve disputes through the use of digital platforms that enable parties to interact without geographical boundaries. This study aims to analyze the relevance, challenges, and changes in legal processes brought about by online arbitration in the modern context. Using a juridical-normative method, the study examines the applicable legal framework, doctrine, and academic literature to understand how digitalization affects arbitration procedures. The analysis shows that online arbitration has strategic value because it can provide efficiency, flexibility, and accessibility not always found in conventional arbitration. However, its implementation still faces various issues, such as data security, technological capability gaps, the integrity of electronic evidence, and the lack of comprehensive legal standards. On the other hand, digitalization has also driven significant changes in the structure of procedural law, including the simplification of procedures and the expansion of the recognition of electronic evidence. This study confirms that the success of online arbitration requires regulatory harmonization, increased technical capacity of the parties, and strengthening of digital infrastructure so that it can function as an effective, fair, and adaptive dispute resolution mechanism to technological developments.